The Influence of Strategic Human Resource Practices and Ethical Leadership on Organizational Performance of Star Hotels: Mediated by Intellectual Capital and Sustainable Competitive Advantage - Lelly Christin; Yolanda Masnita Siagian; Husna Leila Yusran; Justine Tanuwijaya (Dinasti Publisher, 2024)
The study aims to analyze the influence of strategic human resource practices and ethical leadership on organizational performance in star-rated hotels in Jakarta, mediated by intellectual capital and sustainable competitive advantage. It addresses gaps in previous studies by examining both factors simultaneously and introducing decision making based on HR metrics. A quantitative method was employed, collecting data from HR supervisor level in star-rated hotels in Jakarta, with 255 respondents. Hypotheses were tested using PLS-SEM analysis. Results indicate that strategic human resource practices and ethical leadership positively impact organizational performance. Intellectual capital and sustainable competitive advantage mediate this effect. These findings underscore the importance of investing in intellectual capital and sustainable competitive advantage to enhance hotel performance. The study provides a reference for hotel management to develop effective HR and leadership strategies, emphasizing the importance of intellectual capital and competitive advantage. Regular monitoring and evaluation of these strategies are recommended to ensure alignment and positive impacts on hotel performance. Future research should consider adding variables such as technological readiness and innovation capability, given the rapid technological advancements and intense competition in the hospitality industry, which affect hotel performance and competitive advantage.